Nonhypercholesterolemic effects of a palm oil diet in Chinese adults - Jian, Z; Wang, P; Wang, C; Chen, X.S; Ge, K (The Journal of nutrition, 1997)
The effects on serum lipids of palm oil (PA) used in Chinese diets were compared with those of soybean oil (SO), peanut oil (PE) and lard (LA) in normocholesterolemic subjects and with that of PE in hypercholesterolemic subjects. Normocholesterolemic subjects (120 men, 18-25 y, total cholesterol (TC) 2.8-5.0 mmol/L) were assigned to four groups to consume test diets for six consecutive weeks after a run-in period of 3 wk. About 30% of dietary energy was derived from fat, 75-80% of which came from test oils. In comparison with the entry level, the average serum TC and LDL cholesterol (LDL-C) were 6.7 and 13.1% lower, respectively, in the PA group and 22.8 and 30.7% higher, respectively, (P 0.05) in the LA group. At the end of the test, serum TC, LDL-C and the ratio of TC/HDL cholesterol (HDL-C) in the PA group were significantly lower than those of the LA group. Hypercholesterolemic subjects (31 men, 20 women, 32-68 y, TC 5.5-7.0 mmol/L) were divided into two groups. For 6 wk, one group (15 men, 10 women) consumed the PA diet; another group (16 men, 9 women) consumed the PE diet. After a 3-wk interval, the two groups interchanged diets for another 6 wk. The test diets again contained about 30% energy from fat, 60-65% of which came from test oils. Compared with entry values, the PA diet caused significant reductions in serum TC, LDL-C and TC/HDL-C during the first 6 wk and also a significant reduction in TC/HDL-C during the second 6 wk. The PE diet had no significant influence on serum lipids in either experimental period